Interferensi Morfologi Bahasa Pertama terhadap Keterampilan Berbicara Bahasa Arab - Puti Zulharby; Zainal Rafli; Samsi Setiadi (Universitas Mulawarman, 2022)
This study aims to find the form of morphological interference that occurs due to the contact between the Arabic language being studied and the first language that has been mastered by students of Arabic Language Education, State University of Jakarta. This study uses a descriptive qualitative approach with a case study method. The case studies were carried out directly in real life from data sources totalling 95 students. Data collection was carried out through testing, direct interviews and listening to conversations. From this study, it was found that there were 480 forms of morphological interference, which were summarized into the following forms: (1) differences in word patterns (22%); (2) word formation (32%); (3) compounding (3%); and (4) reduplication (43%). Factors causing morphological interference that occur among students are differences in word patterns between Arabic and the first language that has been mastered, low understanding of Arabic vocabulary and systems, and differences in the culture of language users.